Sorption of fluoride ions from aqueous solutions by a yttrium-loaded poly (hydroxamic acid) resin - Haron, M.J.; Wan Yunus, W.M.Z.; Tokunaga, S. (OPA, 1995)
Yttrium‐loaded poly(hydroxamic acid) ion‐exchange resin (YPHA) has been studied to sorb fluoride ion from aqueous solutions. The resin was effective in decreasing the fluoride concentration from 5 mM down to 0.002 mM in the pH range of 2.8 to 4.2. The rate constant for the sorption was found to be 5.6 x 10‐2 min‐1. The sorption of the fluoride was the Langmuir type and its capacity was 0.68 mmol‐F/g resin. The sorption selectivity shows that the fluoride removal may be interfered by the presence of phosphate and sulphate but was not affected by chloride, bromide, iodide and nitrate ions. The removal of fluoride from actual industrial wastewaters was more than 96%. A column test shows that fluoride ion was retained on the column until the breakthrough point. The fluoride ion sorbed can be eluted from the resin with 100 mM sodium hydroxide, and the column can be reused after being conditioned with 1 mM hydrochloric acid.